СВОЕВРЕМЕННОСТЬ И РАЗУМНЫЙ СРОК СУДЕБНОГО РАЗБИРАТЕЛЬСТВА КАК КРИТЕРИИ ЭФФЕКТИВНОСТИ ГРАЖДАНСКОГО СУДОПРОИЗВОДСТВА - ДЖАВАДОВ, Хикмет Аловсат оглы (SUPREMANCE OF LAW, 2016)
Article is devoted to research of influence of time spent for civil legal proceedings for its efficiency. The author recognizes that a factor of time matters for the characteristic of resource intensity of legal proceedings which, in turn, considerably defines its efficiency. The problem of reasonable term of judicial proceedings is considered and its value as criterion of establishment of cases in which efficiency of legal proceedings isn’t reached in view of the excessive duration of process locates. The concept of the optimum procedural term determined by the author as a necessary and suffi cient period for judicial proceedings of business (its part) is analyzed.